RECOVERY KINETIC OF PATIENTS WITH RHEUMATOID ARTHRITIS.(RA) (GYMNASIUM, 2009)
Clinical picture of the hand is complex rheumatoid impaired at multiple osteo-articular, muscle,tendons, ligaments. Lesions at the punch: tenosinovita extensorilor, sinovita radio-carpal, sidrom head cubits,sidrom carpal canal, redoarea punches, especially in the flex, mainly under the action of flexorilor initiallysubluxaţie web subsequently associated with radial deviation of pumnului.Leziuni at the fingers: a fingerdeviatţa cubits. fingers "thrown in the pen, fingers in buttonhole, policele" in Z "tenosinovitele hand. clinicoassessment - functional recovery oriented program, outlines the methodology appropriate to each case, theclinical obiectiveaza obtained by certain procedures, focused on prognosticului.(1)Treatamentof the handreumatoide. Objectives: preserving functional capacity of the rheumatoid hand, primarily from an articularmusculoskeletal, functional capacity preserving outstanding (for each stage of the disease), adjustingactivities according to current restantul functional real functional autonomy by maintaining maximumoperating capacity remaining real(1). Kinetoterapie - Objectives: prevent deformation and vicious attitudes,maintain or increase joint mobility, increase strength and muscle rezisteţei, kinetic treatment should be early,continuous, permanent, adapted evolutionary stage of each patient, the type of deformation adapted existingadapted restantului actual running phase, adapted functional objectives of the needssubiectului.Ergoterapie.(2)